Development of a novel multi-epitope mRNA vaccine candidate to combat HMPV virus - Shiyang Ma; Fei Zhu; Yizhong Xu; Haicheng Wen; Mingjun Rao; Peipei Zhang; Wenzhong Peng; Yanhui Cui; Hang Yang; Caixia Tan; Jie Chen; Pinhua Pan (Human Vaccines & Immunotherapeutics)
Human metapneumovirus (HMPV) is one of the main pathogens causing severe respiratory infections in children, as a common cause of immunodeficiency-related deaths in children and elderly individuals, the prevalence of HMPV has been showing an increasing trend during the last years. However, no vaccines or effective treatment plans are available currently. In this present, based on candidate proteins highly associated with viral virulence and has promising protective potential, we screened for immunodominant cytotoxic T cells, helper T cells, and Linear B-cell epitopes from the most promising candidate Fusion protein, together with G, SH, M, and M2. All epitopes were predicted to have strong antigenicity by Vaxijen and pose no potential toxicity, allergenicity, or hormonology to human proteins by Toxinpred, Allerpred, and Blast analysis, meanwhile, high conservancy is demanded to cover different subtypes. adjuvants β-defensin II and Pam2Cys was attached with EAAAK linkers to improve vaccine’s efficiency. Then, calculation of physicochemical properties proved the protein vaccine as a product can stably exist in the human body. Besides, we assessed the docking between the vaccine and immune receptors to evaluate its ability to stimulate immune responses, and the dynamic simulation further confirmed that the vaccine can tightly bind with immune receptors, which approved that the construction has the potential to induce strong humoral and cellular immune response. Finally, the vaccine was constructed into a multi-epitope mRNA vaccine, the immune simulations suggest that this is a vaccine candidate for controlling HMPV infection.